HUBUNGAN ANTARA PERHATIAN ORANG TUA DENGAN PRESTASI BELAJAR SISWA KELAS IV SDN JOGLO 09 JAKARTA BARAT - Fenisa Qurrota Ayuni; Rizki Zuliani; Moh Zamroni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This study aims to determine the relationship between parental attention and learning achievement of fourth grade students at SDN Joglo 09 West Jakarta. This study used a quantitative survey approach involving 63 fourth grade students from SDN Joglo 09 West Jakarta who participated in this study. Data analysis techniques using descriptive statistics and inferential statistics. In this study the data collection instruments used were questionnaires and observations that were specifically designed to measure parental attention and learning achievement. The results of the study showed that there was a positive relationship between parental attention and fourth grade student achievement. The data collection technique consisted of student scores and 25 parental concern questions using a Likert scale with 4 scales. To test the hypothesis, the correlation coefficient test was used to obtain a value of 0.404, from the t test results obtained t count 3.449 and t table 1.999, it can be concluded that there is a relationship between the school environment and character formation of 16.3%. With the direction of a positive relationship, it means that the more attention parents give to children will increase their learning achievement.